Colorimetric Detection of Uranyl Using a Litmus Test - Manochehry, Sepehr; McConnell, Erin M.; Tram, Kha Q.; Macri, Joseph; Li, Yingfu (Frontiers in Chemistry, 2018)
Ingestion of water containing toxic contaminants above levels deemed safe for human consumption can occur unknowingly since numerous common contaminants in drinking water are colorless and odorless. Uranyl is particularly problematic as it has been found at dangerous levels in sources of drinking water. Detection of this heavy metal-ion species in drinking water currently requires sending a sample to a laboratory where trained personnel use equipment to perform the analysis and turn-around times can be long. A pH-responsive colorimetric biosensor was developed to enable detection of uranyl in water which coupled the uranyl-specific 39E DNAzyme as a recognition element, and an enzyme capable of producing a pH change as the reporter element. The rapid colorimetric assay presented herein can detect uranyl in lake and well water at concentrations relevant for environmental monitoring, as demonstrated by the detection of uranyl at levels below the limits set for drinking water by major regulatory agencies including the World Health Organization (30 µg/L). This simple and inexpensive DNAzyme-based assay enabled equipment-free visual detection of 15 µg/L uranyl, using both solution-based and paper-based pH-dependent visualization strategies.